RUSSIA UKRAINE CONFLICT: EMPACT ON INDIAN ENERGY INDUSTRY (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
The conflict between Russia and Ukraine has significant ramifications for India's energy industry. This is due, in part, to the fact that India is mostly reliant on imported oil and gas, and Russia is a significant supplier of both of these commodities. This abstract's objective is to study the potential consequences that the war may have on India, including disruptions in energy supply chains, price volatility in global markets, and strategic implications for energy security. Specifically, the abstract will aim to investigate these potential repercussions. Due to the fact that India is now experiencing geopolitical conflicts, the research demonstrates the challenges that the country confronts in terms of maintaining stable energy prices and receiving trustworthy supply. In addition to this, it highlights the importance of diversifying energy policy and engaging in diplomatic engagements in order to reduce risks and ensure that energy security is maintained continuously.